FAKTOR-FAKTOR YANG BERHUBUNGAN TERHADAP PERILAKU SAFETY RIDING PADA MAHASISWA FAKULTAS X UNIVERSITAS DIPONEGORO - Dine Wahyu Prima; Bina Kurniawan; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Safety riding is riding a motorcycle behavior by giving priority to the safety of themselves and other road users. Data from Satlantas Polrestabes Semarang during January to April 2015, from 32.340 people affected by 66.5% ticketed status of students. Preliminary survey of Undip known some students still lacking in the practice of safety riding, one of them is Faculty X. The survey of more than 70% of students go to college riding a motorcycle. All respondents, 10 people have good knowledge, while 90% had a foul while riding. The purpose of this research was to determine the related factors to behaviour of safety riding on students of Faculty X Undip. This research used a cross-sectional observational analytic approach. Subjects were 100 student motorcyclists Faculty X Undip. The results were obtained by 51% of respondents behaved safety riding well and 49% of respondents are unsafe. Based on data analysis using chi square obtained related variable was the attitude (p-value: 0.001), the participation of training (p-value: 0.008), and the role of peer group (p-value: 0.028). While unrelated variables were driving period (p-value: 0.435), knowledge (p-value: 0.708), the condition of the motorcycle (p-value: 0.368) and the presence of safety apparels (p-value: 0.430). Researcher suggests held safety riding training on campus environment to improve the knowledge and skills of students in riding a motorcycle.